2016
DOI: 10.1016/j.ihj.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of coronary artery disease in patients with symptomatic bradyarrhythmias requiring pacemaker implantation

Abstract: BackgroundThis study was conducted to assess the prevalence and characterization of CAD in high risk patients requiring pacemaker implantation for symptomatic bradyarrhythmias.MethodsThis study included 100 patients with symptomatic sinus node dysfunction or atrioventricular block, who were at high risk of CAD or had previously documented atherosclerotic vascular disease (ASCVD). Coronary angiography was performed before pacemaker implantation. CAD was defined as the presence of any degree of narrowing in at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…It can be said that such patients should undergo coronary monitoring before undergoing pacemaker surgery. Simultaneous CAD treatment is likely to improve the long-term prognosis of these patients [19]. The findings of the mentioned study on coronary artery disease are more than our study.…”
Section: Discussionmentioning
confidence: 54%
“…It can be said that such patients should undergo coronary monitoring before undergoing pacemaker surgery. Simultaneous CAD treatment is likely to improve the long-term prognosis of these patients [19]. The findings of the mentioned study on coronary artery disease are more than our study.…”
Section: Discussionmentioning
confidence: 54%
“…Brueck et al [6] in an angiographic study of 507 patients requiring pacemaker implantation and at least one atherosclerotic risk factor, found a remarkable 71% incidence of CAD. Alai et al [2] revealed an overall 45% incidence of CAD and 29% incidence of significant CAD in these patients. Our study revealed a prevalence rate of 19.4% of CAD in patients who underwent PPI during 2011-2015.…”
Section: Discussionmentioning
confidence: 93%
“…Bradycardia is a common clinical phenomenon and can be defined as heart rate below 60 bpm. It may also be associated with various rhythmic disorders such as sinus nodal disease (SND) and atrioventricular (AV) blocks [2]. Patients with regular or occasional conduction disturbance who experience symptoms such as fatigue, presyncope or syncope require permanent pacemaker implantation (PPI) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Few small studies have investigated association between conduction disturbance & coronary atherosclerosis. 2 , 3 , 4 , 5 , 6 These studies showed 15–70% association of chronic coronary artery disease in chronic conduction disorders. 7 , 8 , 9 , 10 Coexistence of CAD with symptomatic bradycardia has major effects on prognosis & long term plan of care in form of either medication or revascularization.…”
Section: Introductionmentioning
confidence: 95%
“… 1 These histopathological changes are nonspecific & cannot explain the underlying disorder as these changes can be seen in many pathological conditions like hypertension, congenital heart diseases, myocardial diseases or coronary atherosclerosis. 2 …”
Section: Introductionmentioning
confidence: 99%